Dampak Reputasi Perusahaan dan Media Sosial terhadap Niat Melamar Kerja Gen Z melalui LinkedIn - Andi Indra Saputra Alamsyah; Yizreel Junus Kende; Alisa Alaina; Yuni Astuti (Komunitas Dosen Indonesia, 2024)
This study investigates the simultaneous impact of company reputation and social media information on job applicant intention. Data was collected from a sample of 100 respondents, with descriptive statistics indicating mean values of 40.39 for company reputation, 36.49 for social media information, and 56.68 for job applicant intention. Classical assumption tests confirmed the normal distribution of data, absence of multicollinearity, and lack of heteroscedasticity. Instrument testing showed high reliability and validity of the measurement items. The hypothesis tests revealed that both company reputation and social media information significantly affect job applicant intention. The multiple linear regression analysis indicated that a unit increase in company reputation and social media information results in increases in job applicant intention by 0.467 and 0.706 units, respectively. The partial t-test results showed t-values of 3.005 for company reputation and 5.222 for social media information, both significant at p < 0.05. The simultaneous F-test confirmed the combined effect of these variables, with an F-value of 30.417 and a significance level of 0.000. The findings align with existing research, suggesting that effective employer branding and strategic use of social media significantly enhance a company's reputation and attractiveness to job seekers. Companies with a positive reputation and active social media presence are more successful in attracting high-quality candidates, highlighting the importance of these factors in modern recruitment strategies. In conclusion, maintaining a positive company reputation and leveraging social media are crucial for increasing job applicant intention. These strategies not only improve the perception of the company as a desirable workplace but also significantly boost the likelihood of attracting potential job candidates. This study underscores the importance of integrating employer branding and social media efforts to enhance recruitment outcomes